Implementation of P5 Local Wisdom Theme: Life of Padang Coastal Communities by SMAN 1 Padang - Ritagustiani, Ritagustiani; Erianjoni, Erianjoni; Indrawadi, Junaidi; Febriani, Eka Asih (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2025)
This research aims to identify the process of implementing P5 themed on local wisdom in coastal Padang Beach, explore traditions such as rabana, pukkek, and soccer, and develop learners' social competencies. In addition, the research measured the impact of P5 and provided recommendations for future program improvements. The research method is field qualitative with a descriptive approach. Data were collected through observation, interviews, and documentation. Data analysis used the Miles and Huberman model: data reduction, data presentation, and conclusion drawing. The results of this study reveal that the implementation of the Pancasila Student Profile Strengthening Project (P5) with the theme of local wisdom at SMAN 1 Padang is a learning platform that enriches students' character and cultural awareness. Through a careful preparation stage, the school formed a team of facilitators and developed a module to guide students to understand Padang's coastal culture in depth. In the implementation phase, students interacted directly with the Ulak Karang Utara community, learning the art of rabana that strengthens togetherness, as well as fishing techniques with pukkek that reflect the spirit of mutual cooperation. This experience broadened students' horizons about cultural resilience, cooperation, and the importance of preserving local heritage. Evaluation is conducted through portfolios that record student and educator reflections, revealing successes in building pride in local culture as well as challenges that need to be refined, such as expanding collaboration with community institutions. Overall, the implementation of P5 not only deepens students' cultural understanding, but also reinforces the values of Pancasila in their daily lives. With the sustainability of the program and the support of various parties, this model has the potential to become an inspiration for other schools in Indonesia, integrating character education with the preservation of local culture as a foundation for strengthening national identity.